Unveiling the Synergies of Hyponymy, Hierarchy, and Taxonomy: Understanding Semantic Relationships and Organizational Structures ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Language is an intricate system that allows us to communicate and understand the world around us. In the study of linguistics, the concepts of hyponymy, hierarchy, and taxonomy provide a deeper understanding of how words relate to each other and how we categorize information. This article aims to delve into these notions, shedding light on their significance and exploring their applications in various fields. This article explores the intertwined concepts of hyponymy, hierarchy, and taxonomy, focusing on their definitions, types, applications, and synergies. It analyzes the significance of hyponymy in lexical semantics, identifies the various types of hierarchy, and delves into the purpose and applications of taxonomy in diverse fields. The article highlights the connections and interplay between these notions, emphasizing their role in semantic understanding, knowledge organization, and efficient information retrieval